Stock return ignorance - Merkoulova, Yulia; Veld, Chris (Journal of Financial Economics, 2022)
Optimal stock investment decisions rely on assessments of the distribution of expected returns. Using a representative sample, we find over half the US population cannot answer simple questions on expected stock returns. Respondents who are unable to make any return prediction, who cannot answer questions on the distribution of expected returns, or who reveal unlikely distributional beliefs participate less in the stock market and have smaller stock investments. However, overoptimistic investors are more likely to participate in the stock market and have larger stock investments. These results persist after controlling for financial literacy, intelligence, education, and demographics. People who are ignorant about stock return distribution are more likely to invest in equities if they have higher levels of trust. Therefore, trust can substitute for cognition as a factor positively associated with individuals’ propensity to invest.